# cos(A+B)=cos(A-(-B))=cosAcosB(-B)+sinAsin(-B) therefore cos(A+B)=coaAcosB-sinAsinB

**mathew**

cos(A+B)=cos(A-(-B))=cosAcosB(-B)+sinAsin(-B) therefore cos(A+B)=coaAcosB-sinAsinB

- 9 years ago
- 999999.99

**Answer(0)**

**Bids(0)**

**other Questions(10)**

- strongest long-lasting natural fabric
- An interest rate of 13,75% compounded monthly is equivalent to a daily compounded interest rate of
- help with literature work
- 6-5-11+7-9=-59
- Accounting
- -8 - 7t^2 t=-3
- purchased office equipment for 5500 on credit payable in 30 days
- Persuasive essay?
- If you cash a $475 traveler’s check at a bank, by how much do(es) m2 change?
- if the diameter of a circular plastic swimming pool is 6 feet, then the area of the bottom of the...

**Tips(0)**